Morphine Sleep in Pregnancy - Mackeen, A. Dhanya; Fehnel, Eric; Berghella, Vincenzo; Klein, Thomas (American Journal of Perinatology, 2014)
Objectives To determine the incidence of admission in labor after morphine sleep (therapeutic rest), patient characteristics associated with labor, and adverse outcomes associated with treatment.Methods We reviewed medical records of women treated with morphine sleep from December 2005 to December 2009. Variables evaluated included medications used for treatment, cervical examination, maternal demographic characteristics and obstetric history, fetal heart rate patterns, and maternal/neonatal outcomes. These characteristics were compared between those admitted in labor after morphine sleep versus those discharged.Results Fifty-eight women received morphine sleep: 36 (62%) were admitted in labor, 17 (29%) were discharged, and 5 (9%) were admitted secondary to category II fetal heart rate tracings. All fetuses had category I fetal heart rate tracings prior to treatment. Median dose of morphine sulfate was 20 mg. Those with effacement > 50% (p < 0.01) and carrying term gestations (p < 0.01) were more likely to be admitted in labor after treatment. There were no adverse maternal outcomes. There were no significant differences in neonatal outcomes.Conclusion Sixty-two percent of women were admitted in labor after morphine sleep. Admission effacement > 50% and term gestational age were associated with admission in labor. There were no significant differences in maternal or neonatal morbidity in those admitted versus discharged home after treatment with morphine sleep.
Keywords: labor dysfunction; latent labor; therapeutic rest; morphine sleep